Tests and exercises for the spine - Fischer, Peter (Physical therapist) (Thieme, 2015)
Tests and Exercises for the Spine expertly guides physical therapists in conducting tests to help determine which exercises are most effective in treating each patient's particular spinal condition. It is a concise, practical manual in which the evaluation (test), therapy (exercise), and home exercise program are presented in a single step,saving physical therapists and patients time and increasing the sustainability of the treatment